1997
DOI: 10.1177/0887302x9701500302
|View full text |Cite
|
Sign up to set email alerts
|

Managing Variation In Textile Science Abstracts and Reports Through A Comprehensive Format and Generic Structure

Abstract: Analysis of published textile science research papers revealed structural and rhetorical variations within and across published works suggesting that the needs and expectations of readers were not being met. This paper proposes a format and generic structure for both abstracts and full research papers so that written works in textile science are effective tools of communication. The format and structure identifies eleven critical elements and suggests a framework that helps readers of research recognize the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Finally, of those articles with a theoretical perspective, 3.1% (f = 7) focused on aesthetics and design, 2.7% (f = 6) had a historic focus, 0.9% (f = 2) addressed construction, whereas 0.4% (f = 1) were journal analyses. These results are fairly consistent with those of Hutton (1984) for the overall percentage of articles that articulated a theoretical framework and with those of Kadolph and Scheller (1997) for the extent to which the textile science articles they analyzed specified a theoretical framework.…”
Section: Descriptive Analysessupporting
confidence: 78%
See 3 more Smart Citations
“…Finally, of those articles with a theoretical perspective, 3.1% (f = 7) focused on aesthetics and design, 2.7% (f = 6) had a historic focus, 0.9% (f = 2) addressed construction, whereas 0.4% (f = 1) were journal analyses. These results are fairly consistent with those of Hutton (1984) for the overall percentage of articles that articulated a theoretical framework and with those of Kadolph and Scheller (1997) for the extent to which the textile science articles they analyzed specified a theoretical framework.…”
Section: Descriptive Analysessupporting
confidence: 78%
“…Finally, like Kadolph and Scheller (1997), we urge researchers to think about how their published research articles are used by graduate students and other scholars. Those authors found that in textile science reports, researchers did not always articulate essential elements of the research.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations